2021
DOI: 10.1016/j.psychres.2021.113776
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Infection Prevention, Testing Data, and Clinical Outcomes of COVID-19 on Five Inpatient Psychiatric Units in a large Academic Medical Center

Abstract: Inpatient psychiatric facilities can face significant challenges in containing infectious outbreaks during the COVID-19 pandemic. The main objective of this study was to characterize the epidemiology, testing data, and containment protocols of COVID-19 in a large academic medical center during the height of the COVID-19 outbreak. A retrospective cohort analysis was conducted on hospitalized individuals on five inpatient psychiatric units from March 1 st to July 8 th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Our findings suggest that admission volume was heavily impacted by structural changes in response to COVID-19 infection prevention standards, and not fully a function of reductions due to lessened demand. For example, we developed a COVID+ inpatient psychiatry unit for 4 weeks that impacted inpatient bed volumes (decreased number of beds on one unit) ( Li et al., 2021 ; Luming Li et al., 2020 ). In addition, we made accommodations to temporarily reduce inpatient volume capacity to meet social distancing requirements and to quarantine patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that admission volume was heavily impacted by structural changes in response to COVID-19 infection prevention standards, and not fully a function of reductions due to lessened demand. For example, we developed a COVID+ inpatient psychiatry unit for 4 weeks that impacted inpatient bed volumes (decreased number of beds on one unit) ( Li et al., 2021 ; Luming Li et al., 2020 ). In addition, we made accommodations to temporarily reduce inpatient volume capacity to meet social distancing requirements and to quarantine patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported during other Coronavirus infections 3 . Importantly, further studies showed an increased risk for a SARS-CoV-2 infection and a more severe course of COVID-19 in psychiatric patients 11 21 22 25 , although comorbidity may have an important role therein. Comorbid medical conditions are frequent, especially in severe mental disorders, leading to reduced life expectancy; if they are accounted for, increased COVID-19 mortality rates in mental disorders were no longer observed 57 .…”
Section: Discussionmentioning
confidence: 94%
“…Vice versa, Taquet et al 11 reported that patients suffering from a mental illness (particularly mood disorders, anxiety disorders, or psychotic disorders) showed an increased risk for COVID-19. Further, patients with mental disorders have been reported to have a more severe outcome of COVID-19, including admission to an intensive care unit and death, as evidenced by numerous studies 19 20 21 22 23 24 21 25 26 and corroborated by a meta-analysis 20 . The same seems to hold true for a pre-existing substance abuse disorder 27 .…”
Section: Introductionmentioning
confidence: 93%
“…The Gantt chart can be used in several situations, each with a particular view, with the intention to evaluate “temporal dependencies” [ 38 ]. It was used to tell the “historiophoty” of a university department [ 39 ], and, more recently, to describe the clinical course of COVID-19 cases across time [ 40 ], and to describe cases of COVID-19 in some psychiatric facilities [ 41 ].…”
Section: Discussionmentioning
confidence: 99%